The long-term effects of gold nanoparticles as gene vectors in a 6 hydroxydopamine-induced parkinsonian rat model - Siobhan van der Vyver; Musa V. Mabandla; Zama N.P. Msibi (Brain Disorders)
Nanotechnology is a growing field that has widely documented the surface binding capabilities of gold nanoparticles (AuNPs). This makes them potentially useful gene vectors for the transfer of defective enzymes in Parkinson's disease (PD), a neurodegenerative disorder resulting in neuroinflammation and neuronal cell destruction. We investigated the long-term effects of AuNPs in the striatum of a 6-hydroxydopamine (6-OHDA)-induced parkinsonian rat model. AuNP-conjugated transgene constructs (AuNP-DNA) of human aromatic acid decarboxylase (AADC) mixed with GTP cyclohydrolase 1 (GCH1) (1:1) was stereotaxically delivered to the striatum of either saline or 6-ODHA-lesioned Sprague Dawley rats. Long-term effects of AuNP-mediated gene therapy were evaluated on behavior, pro-inflammatory cytokine IL-1β expression, morphology of striatal microglia, dopamine biosynthesis and transgene expression. The 6-OHDA-induced neurobehavioral deficits were mitigated in gene therapy groups. This finding was correlated with significantly improved dopamine biosynthesis, inhibition of long-term expression of IL-1β, and suppression of sustained microglial activation. Both human AADC and GCH1 transgenes were differentially expressed in the groups that underwent gene therapy. This suggests a successful AuNP-mediated transgene expression in the striatum, allowing for effective uptake and transcription of AADC and GCH1 for DA re-synthesis. Furthermore, an IL-1β- and microglial-mediated inflammatory response was attenuated, preventing or suppressing neuroinflammation that is implicated in PD pathology. Further studies detailing the mechanism of cellular uptake and transgene expression may be useful in determining the success of AuNPs as gene vectors in PD treatment.